Method of producing pressure-sensitive adhesive layer attached one-side protection polarizing film
Patent Information
- Application Number
- KR1020230190208
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2014-01-07
- Filing Date
- 2023-12-22
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2034-10-24
Smart Images

Figure R1020230190208_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a polarizing film with an adhesive layer formed thereon, wherein a transparent protective film is laminated on only one side of a polarizer, and an adhesive layer is directly laminated on the other side. The polarizing film with an adhesive layer formed thereon obtained by the manufacturing method can form an image display device such as a liquid crystal display (LCD), an organic EL display, a CRT, or a PDP, either alone or as an optical film laminated thereon. Background Technology
[0002] Liquid crystal displays are rapidly expanding into the market for devices such as watches, mobile phones, PDAs, laptop PCs, PC monitors, DVD players, and TVs. Liquid crystal displays visualize the polarization state resulting from the switching of liquid crystals, and polarizers are used in this display principle.
[0003] As for polarizers, iodine-based polarizers with a stretched structure, for example, by adsorbing iodine onto polyvinyl alcohol, are the most commonly and widely used due to their high transmittance and high polarization degree. However, such polarizers have the disadvantage of having extremely weak mechanical strength and shrinking due to heat or moisture, which significantly degrades their polarization function. Therefore, the obtained polarizer is immediately laminated with a transparent protective film coated with adhesive through an adhesive, and is used as a polarizing film.
[0004] In addition, when attaching a polarizing film to a liquid crystal cell, an adhesive is typically used. Furthermore, since the bonding of the polarizing film and the liquid crystal cell typically reduces light loss, each material is bonded using an adhesive. In such cases, a polarizing film is generally used in which an adhesive layer is formed as an adhesive layer on one side of the polarizing film, as the adhesive has advantages such as not requiring a drying process to fix the polarizing film.
[0005] Meanwhile, image display devices such as liquid crystal displays are becoming thinner, and thinning is also required for polarizing films formed with adhesive layers. For example, by stretching and dyeing a laminate having a resin substrate and a polyvinyl alcohol-based resin layer formed on one side of the resin substrate, a polarizer made of a thin polarizing film can be obtained on the resin substrate (Patent Document 1). In addition, a polarizing film formed with an adhesive layer, in which a transparent protective film is formed only on one side of the polarizer and an adhesive layer is formed directly without forming a transparent protective film on the other side, can achieve a thinning form because the transparent protective film is one less than that of a conventional polarizing film formed with an adhesive layer, in which a transparent protective film is formed on both sides of the polarizer. Prior art literature
[0006] Japanese Published Patent Application No. 2000-338329 The problem to be solved
[0007] Liquid crystal display devices are required to satisfy adhesion even under harsh conditions, such as high temperature or high temperature and high humidity, and to possess durability that prevents appearance defects. The above durability is also required for the adhesive layer associated with the protective polarizing film on which the above adhesive layer is formed.
[0008] In addition, when manufacturing a protective polarizing film with an adhesive layer formed thereon using a polarizer consisting of a thin polarizing film formed on one side of the resin substrate above, a transparent protective film is laminated with an adhesive interposed on the polarizer (polarizing film) first, and then, after peeling off the resin substrate, an adhesive layer is laminated on the other side of the polarizer where the peeling operation was performed, thereby producing a protective polarizing film with an adhesive layer formed thereon. However, a protective polarizing film with an adhesive layer formed thereon obtained by this conventional manufacturing method has not been obtained that satisfies durability.
[0009] The present invention aims to provide a method for manufacturing a polarizing film having an adhesive layer formed thereon that satisfies durability even when applied to a thin polarizer. means of solving the problem
[0010] As a result of repeated careful consideration to solve the above problem, the inventors discovered a method for manufacturing a protective polarizing film having the following adhesive layer formed thereon, and completed the present invention.
[0011] That is, the present invention comprises a process (1) of preparing a partial protection polarizing film having a resin substrate formed thereon, the resin substrate having a polarizer formed on one side of the resin substrate and a transparent protective film laminated on the polarizer side, and,
[0012] A process (2) for peeling off the resin substrate from the protective polarizing film on which the resin substrate is formed, and
[0013] A process (3) for performing an activation treatment on the surface of a polarizer from which the resin substrate has been peeled off by the above process (2) under conditions of an integrated irradiation amount of activation energy of 0.01 to 2 J / ㎠, and
[0014] The present invention relates to a method for manufacturing a polarizing film having an adhesive layer formed thereon, characterized by having a process (4) of directly laminating an adhesive layer on the surface of a polarizer on which the above process (3) is performed.
[0015] In the method for manufacturing a protective polarizing film having the above adhesive layer formed thereon, corona treatment, plasma treatment, or excimer treatment is preferably employed as the activation treatment of the above process (3).
[0016] In the method for manufacturing a protective polarizing film having the above adhesive layer formed thereon, it is preferable that the thickness of the polarizer is 10 μm or less.
[0017] In addition, in a method for manufacturing a protective polarizing film having an adhesive layer formed thereon, the polarizer is a polarizing film of a continuous web made of a polyvinyl alcohol-based resin oriented with a dichromatic material, and furthermore, a laminate comprising a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate is obtained by stretching through a two-stage stretching process consisting of aerial-assisted stretching and boric acid underwater stretching.
[0018] In a method for manufacturing a protective polarizing film having the above-mentioned adhesive layer formed thereon, it is preferable that the resin substrate is an ester-based resin substrate.
[0019] In the method for manufacturing a protective polarizing film having the above adhesive layer formed thereon, the adhesive layer laminated in the above process (4) is preferably an acrylic adhesive layer.
[0020] In a method for manufacturing a protective polarizing film having the above-mentioned adhesive layer formed thereon,
[0021] Between the above process (2) and the above process (3),
[0022] After the resin substrate is peeled off by the above process (2), a surface protection film is laminated onto the surface of the polarizer and then peeled off. Effects of the invention
[0023] In a conventional method for manufacturing a polarizing film with an adhesive layer, the resin substrate is peeled off from a polarizing film with a resin substrate, and then the adhesive layer is laminated directly onto the surface of a polarizer (e.g., a polyvinyl alcohol-based resin film). However, it was found that foreign substances, such as the material of the resin substrate (oligomer, etc.), remain on the surface of the polarizer following the peeling of the resin substrate. Furthermore, it was found that when the adhesive layer is laminated directly onto the polarizer surface in a state where the foreign substances remain, the foreign substances are incorporated into the adhesive layer. It is believed that these foreign substances not only impair the adhesion (anchoring) between the polarizer and the adhesive layer but also crystallize and precipitate within the adhesive layer to form black spots, thereby causing appearance defects. Additionally, it was found that even if the foreign substances are not observed during the inspection at the time of shipment of the polarizing film with the adhesive layer, they may precipitate over time to form black spots.
[0024] In the present invention, after peeling off the resin substrate from a polarizing film having a resin substrate formed thereon, an activation treatment is performed on the surface of the polarizer, and subsequently, an adhesive layer is directly laminated onto the surface of the polarizer that has been activated. Through this activation treatment, the foreign substances remaining on the surface of the polarizer can be reduced. As a result, a polarizing film having an adhesive layer formed thereon can be obtained that satisfies durability related to adhesion and appearance defects.
[0025] In addition, in the present invention, it is desirable to control the activation energy in the activation treatment to a predetermined range so that deterioration or alteration of the polarizer does not occur during the activation treatment. Deterioration of the polarizer is likely to occur when a thin polarizer is used. Control of the activation energy is desirable when the polarizer used in the polarizer protection polarizing film formed on a resin substrate is a thin polarizer. Accordingly, the polarizer protection polarizing film formed with an adhesive layer obtained by the manufacturing method of the present invention can satisfy optical properties (e.g., optical durability) comparable to those of a polarizer that has not undergone activation treatment, even when a thin polarizer is used.
[0026] In addition, to further improve the adhesion strength between the polarizer and the transparent protective film, it has been proposed to manufacture a polarizing film by laminating the polarizer and the transparent protective film after performing an activation treatment on the surface of the polarizer where the adhesive layer is formed (Japanese Patent Publication No. 2009-008660). However, the said publication has the task of improving the adhesion strength between the polarizer and the transparent protective film. Furthermore, no foreign substances remain on the surface of the polarizer described in the said publication. Brief explanation of the drawing
[0027] FIG. 1 is a conceptual diagram showing an example of an embodiment related to the method of manufacturing a protective polarizing film having an adhesive layer formed thereon according to the present invention. FIG. 2 is a conceptual diagram showing an example of an embodiment related to the method of manufacturing a protective polarizing film having an adhesive layer formed thereon according to the present invention. Specific details for implementing the invention
[0028] The following describes a method for manufacturing a polarizing film with an adhesive layer formed thereon according to the present invention. The polarizing film with an adhesive layer formed thereon according to the present invention has a transparent protective film formed on one side of a polarizer, and an adhesive layer directly laminated on the other side of the polarizer. The polarizing film with an adhesive layer formed thereon according to the present invention is obtained by sequentially performing processes (1) to (4) on a polarizing film with a resin substrate formed thereon. Processes (1) to (4) are described below with reference to FIG. 1. Additionally, as shown in FIG. 2, a process (5) may be included between process (2) and process (3).
[0029] <Process (1)>
[0030] In process (1), a partial protection polarizing film (A) is prepared having a resin substrate (3) and a polarizer (1) formed on one side of the resin substrate (3), and a transparent protection film (2) laminated on the side of the polarizer (1).
[0031] ≪Suji Record≫
[0032] Various thermoplastic resins may be used as the forming material for the resin substrate. Examples of thermoplastic resins include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, ester resins are preferred due to ease of manufacturing and cost reduction. As for the ester thermoplastic resin substrate, an amorphous ester thermoplastic resin substrate or a crystalline ester thermoplastic resin substrate may be used.
[0033] Various types of polarizers may be used as the above-mentioned polarizer. Polarizers obtained by various manufacturing methods may be used. The thickness of the above-mentioned polarizer is typically 30 μm or less, but the manufacturing method of the present invention is preferably applied even when using a thin polarizer with a thickness of 10 μm or less. From the perspective of thinning, it is preferable that the thickness of the above-mentioned polarizer be 1 to 7 μm. Such a thin polarizer is desirable in that it has minimal thickness non-uniformity, excellent visibility, and excellent durability due to minimal dimensional change, and furthermore, the thickness of the polarizing film can be thinned.
[0034] Thin Polarizer
[0035] Representative examples of thin polarizers include the thin polarizing films described in Japanese Patent Publication No. Sho 51-069644, Japanese Patent Publication No. 2000-338329, the pamphlet of WO2010 / 100917, the specification of PCT / JP2010 / 001460, or the specification of Japanese Patent Application No. 2010-269002 and Japanese Patent Application No. 2010-263692. These thin polarizing films can be obtained by a manufacturing method comprising a process of stretching a polyvinyl alcohol-based resin layer (hereinafter also referred to as a PVA-based resin) and a stretching resin substrate in a laminated state, and a dyeing process. With this manufacturing method, even if the PVA-based resin layer is thin, it is supported by the stretching resin substrate, making it possible to stretch without problems such as breakage due to stretching.
[0036] The above thin polarizing film is preferably obtained by a manufacturing method that includes a process of stretching in an aqueous boric acid solution, such as that described in the specification of WO2010 / 100917, PCT / JP2010 / 001460, or Japanese Patent Application No. 2010-269002 or Japanese Patent Application No. 2010-263692, in order to improve polarization performance by allowing stretching at a high magnification, and in particular, it is preferably obtained by a manufacturing method that includes an auxiliary process of air stretching before stretching in an aqueous boric acid solution, as described in Japanese Patent Application No. 2010-269002 or Japanese Patent Application No. 2010-263692.
[0037] The thin high-performance polarizing film described in the specification of PCT / JP2010 / 001460 above is a thin high-performance polarizing film having a thickness of 7 μm or less, made of a PVA-based resin having a dichromatic material oriented thereon and formed integrally on a resin substrate, and has optical properties having a single transmittance of 42.0% or more and a polarization degree of 99.95% or more.
[0038] The above thin high-performance polarizing film can be manufactured by forming a PVA-based resin layer on a resin substrate having a thickness of at least 20 μm by coating and drying a PVA-based resin, immersing the formed PVA-based resin layer in a dyeing solution of a dichromatic material to adsorb the dichromatic material onto the PVA-based resin layer, and stretching the PVA-based resin layer with the adsorbed dichromatic material integrally with the resin substrate in an aqueous boric acid solution such that the total stretching ratio is at least 5 times the original length.
[0039] In addition, a method for manufacturing a laminated film comprising a thin high-performance polarizing film oriented with a dichromatic material comprises: a step of producing a laminated film comprising a resin substrate having a thickness of at least 20 μm and a PVA-based resin layer formed by coating and drying an aqueous solution containing a PVA-based resin on one side of the resin substrate; a step of adsorbing a dichromatic material onto a PVA-based resin layer included in the laminated film by immersing the laminated film comprising the resin substrate and the PVA-based resin layer formed on one side of the resin substrate in a dyeing solution containing a dichromatic material; a step of stretching the laminated film comprising the PVA-based resin layer adsorbed with the dichromatic material in an aqueous boric acid solution such that the total stretching ratio is 5 times or more of the original length; and a PVA-based resin layer formed by integrally stretching the PVA-based resin layer adsorbed with the dichromatic material on one side of the resin substrate, having a thickness of 7 μm or less and a single transmittance of 42.0% or more. The thin high-performance polarizing film can be manufactured by including a process for manufacturing a laminated film having a thin high-performance polarizing film having optical properties of a polarization degree of 99.95% or more.
[0040] In the present invention, as a polarizer having a thickness of 10 μm or less, a polarizing film of a continuous web made of a PVA-based resin oriented with a dichromatic material may be used, which is obtained by stretching a laminate comprising a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate through a two-stage stretching process consisting of air-assisted stretching and boric acid water stretching. As the thermoplastic resin substrate, an amorphous ester-based thermoplastic resin substrate or a crystalline ester-based thermoplastic resin substrate is preferred.
[0041] The thin polarizing film of the specification of the aforementioned Japanese Patent Application No. 2010-269002 or Japanese Patent Application No. 2010-263692 is a polarizing film of a continuous web composed of a PVA-based resin oriented with a dichromatic material, wherein a laminate comprising a PVA-based resin layer formed on an amorphous ester-based thermoplastic resin substrate is stretched by a two-stage stretching process consisting of air-assisted stretching and boric acid water stretching to obtain a thickness of 10 μm or less. For this thin polarizing film, when the single transmittance is T and the degree of polarization is P, P > -(10 0.929T-42.4 It is desirable to have optical properties that satisfy the conditions of -1) × 100 (where T < 42.3) and P ≥ 99.9 (where T ≥ 42.3).
[0042] Specifically, the thin polarizing film can be manufactured by a method for manufacturing a thin polarizing film comprising: a process of producing a stretched intermediate product consisting of an oriented PVA-based resin layer by high-temperature air stretching of a PVA-based resin layer formed on an amorphous ester-based thermoplastic resin substrate of a continuous web; a process of producing a colored intermediate product consisting of a PVA-based resin layer oriented with a dichromatic material (preferably iodine or a mixture of iodine and an organic dye) by adsorption of a dichromatic material onto the stretched intermediate product; and a process of producing a polarizing film having a thickness of 10 μm or less consisting of a PVA-based resin layer oriented with a dichromatic material by stretching of the colored intermediate product in water with boric acid.
[0043] In this manufacturing method, it is preferable that the total stretching ratio of the PVA-based resin layer formed on an amorphous ester-based thermoplastic resin substrate by high-temperature air stretching and boric acid water stretching be 5 times or more. The liquid temperature of the boric acid aqueous solution for boric acid water stretching can be 60°C or higher. Before stretching the colored intermediate product in the boric acid aqueous solution, it is preferable to perform an insolubilization treatment on the colored intermediate product, and in that case, it is preferable to perform the treatment by immersing the colored intermediate product in a boric acid aqueous solution at a liquid temperature not exceeding 40°C. The above amorphous ester-based thermoplastic resin substrate may be an amorphous polyethylene terephthalate comprising copolymerized polyethylene terephthalate copolymerized with isophthalic acid, copolymerized polyethylene terephthalate copolymerized with cyclohexanedimethanol, or other copolymerized polyethylene terephthalates, and is preferably made of a transparent resin, and its thickness may be at least 7 times the thickness of the PVA-based resin layer being formed. In addition, the stretching ratio of the high-temperature air stretching is preferably 3.5 times or less, and the stretching temperature of the high-temperature air stretching is preferably above the glass transition temperature of the PVA-based resin, specifically in the range of 95°C to 150°C. When the high-temperature air stretching is performed as free-end uniaxial stretching, the total stretching ratio of the PVA-based resin layer formed on the amorphous ester-based thermoplastic resin substrate is preferably 5 times or more and 7.5 times or less. In addition, when high-temperature air stretching is performed as fixed-end uniaxial stretching, it is preferable that the total stretching ratio of the PVA-based resin layer formed on an amorphous ester-based thermoplastic resin substrate is 5 times or more and 8.5 times or less.
[0044] More specifically, a thin polarizing film can be manufactured by the following method.
[0045] A substrate for a continuous web of isophthalic acid copolymerized polyethylene terephthalate (amorphous PET) copolymerized with 6 mol% isophthalic acid is prepared. The glass transition temperature of amorphous PET is 75°C. A laminate consisting of the amorphous PET substrate of the continuous web and a polyvinyl alcohol (PVA) layer is prepared as follows. For reference, the glass transition temperature of PVA is 80°C.
[0046] An amorphous PET substrate with a thickness of 200 μm and an aqueous PVA solution with a concentration of 4 to 5% are prepared by dissolving PVA powder with a degree of polymerization of 1000 or more and a degree of saponification of 99% or more in water. Next, the aqueous PVA solution is coated onto the amorphous PET substrate with a thickness of 200 μm and dried at a temperature of 50 to 60°C to obtain a laminate in which a 7 μm thick PVA layer is formed on the amorphous PET substrate.
[0047] A laminate containing a 7 μm thick PVA layer is subjected to the following process, which includes a two-stage stretching process of air-assisted stretching and boric acid underwater stretching, to manufacture a thin, high-performance polarizing film with a thickness of 3 μm. By the first stage of the air-assisted stretching process, the laminate containing the 7 μm thick PVA layer is stretched integrally with an amorphous PET substrate to produce a stretched laminate containing a 5 μm thick PVA layer. Specifically, this stretched laminate is produced by applying the laminate containing the 7 μm thick PVA layer to a stretching device placed in an oven set to a stretching temperature environment of 130°C, and stretching it along a single free end axis such that the stretching ratio is 1.8 times. Through this stretching treatment, the PVA layer contained in the stretched laminate is transformed into a 5 μm thick PVA layer in which PVA molecules are oriented.
[0048] Next, a colored laminate is produced by adsorbing iodine onto a 5 μm thick PVA layer in which PVA molecules are oriented through a dyeing process. Specifically, this colored laminate is produced by adsorbing iodine onto the PVA layer contained in the stretched laminate by immersing the stretched laminate in a dyeing solution containing iodine and potassium iodide at a liquid temperature of 30°C for an arbitrary amount of time such that the single transmittance of the PVA layer constituting the finally produced high-performance polarizing film becomes 40 to 44%. In this process, the dyeing solution uses water as a solvent, with the iodine concentration within the range of 0.12 to 0.30 wt% and the potassium iodide concentration within the range of 0.7 to 2.1 wt%. The ratio of iodine to potassium iodide concentrations is 1 to 7. For reference, potassium iodide is required to dissolve iodine in water. More specifically, by immersing the stretched laminate in a dyeing solution with an iodine concentration of 0.30 wt% and a potassium iodide concentration of 2.1 wt% for 60 seconds, a colored laminate is produced in which iodine is adsorbed onto a 5 μm thick PVA layer in which PVA molecules are oriented.
[0049] In addition, by means of a second stage boric acid underwater stretching process, the colored laminate is further stretched integrally with the amorphous PET substrate to produce an optical film laminate comprising a PVA layer constituting a high-performance polarizing film with a thickness of 3 μm. Specifically, this optical film laminate is produced by applying the colored laminate to a stretching device placed in a processing device set in a boric acid aqueous solution containing boric acid and potassium iodide at a liquid temperature range of 60 to 85°C, and stretching it along a single free end axis such that the stretching ratio is 3.3 times. More specifically, the liquid temperature of the boric acid aqueous solution is 65°C. Furthermore, the boric acid content is 4 parts by weight per 100 parts by weight of water, and the potassium iodide content is 5 parts by weight per 100 parts by weight of water. In this process, the colored laminate with adjusted iodine adsorption amount is first immersed in the boric acid aqueous solution for 5 to 10 seconds. After that, the colored laminate is passed as is between multiple sets of rolls with different peripheral speeds, which are stretching devices placed in a processing device, and stretched in a single free end axis over 30 to 90 seconds so that the stretching ratio becomes 3.3 times. Through this stretching treatment, the PVA layer contained in the colored laminate is transformed into a 3 μm thick PVA layer in which adsorbed iodine is highly oriented in one direction as a polyiodide ion complex. This PVA layer constitutes a high-performance polarizing film of the optical film laminate.
[0050] In addition, although not an essential process for manufacturing the optical film laminate, it is preferable to remove the optical film laminate from the aqueous boric acid solution by means of a cleaning process and to clean the boric acid attached to the surface of the 3 μm thick PVA layer formed on the amorphous PET substrate with an aqueous potassium iodide solution. Afterward, the cleaned optical film laminate is dried by a drying process using hot air at 60°C. Furthermore, the cleaning process is a process for eliminating appearance defects such as boric acid precipitation.
[0051] [Other processes]
[0052] The above method for manufacturing a thin polarizing film may include other processes in addition to the above process. Examples of other processes include an insolubilization process, a crosslinking process, and a drying (moisture content control) process. Other processes may be performed at any appropriate timing.
[0053] The above insolubilization process is typically carried out by immersing a PVA-based resin layer in an aqueous boric acid solution. By performing the insolubilization treatment, water resistance can be imparted to the PVA-based resin layer. The concentration of the aqueous boric acid solution is preferably 1 to 4 parts by weight per 100 parts by weight of water. The liquid temperature of the insolubilization bath (aqueous boric acid solution) is preferably 20°C to 50°C. Preferably, the insolubilization process is carried out after the fabrication of the laminate and before the dyeing process or the underwater stretching process.
[0054] The above crosslinking process is typically carried out by immersing a PVA-based resin layer in an aqueous boric acid solution. By performing the crosslinking treatment, water resistance can be imparted to the PVA-based resin layer. The concentration of the aqueous boric acid solution is preferably 1 to 4 parts by weight per 100 parts by weight of water. Furthermore, when performing the crosslinking process after the dyeing process, it is preferable to additionally incorporate an iodide. By incorporating the iodide, the leaching of iodine adsorbed onto the PVA-based resin layer can be suppressed. The amount of iodide incorporated is preferably 1 to 5 parts by weight per 100 parts by weight of water. Specific examples of the iodide are as described above. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably 20°C to 50°C. Preferably, the crosslinking process is carried out before the second boric acid water stretching process. In a preferred embodiment, the dyeing process, the crosslinking process, and the second boric acid underwater stretching process are carried out in this order.
[0055] ≪Transparent Protective Film≫
[0056] In process (1), a protective polarizing film (A) formed on a resin substrate is prepared, and a transparent protective film (2) is laminated on the polarizer (1) of a laminate (e.g., the optical laminate obtained above) having a polarizer (1) on one side of the resin substrate (3). Additionally, the polarizer (1) and the transparent protective film (2) are typically laminated with an adhesive layer interposed therein. However, the adhesive layer is not shown in FIG. 1 and FIG. 2.
[0057] The material constituting the above transparent protective film preferably has excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc. Examples include polyester-based polymers such as polyethylene terephthalate or polyethylene naphthalate, cellulose-based polymers such as diacetylcellulose or triacetylcellulose, acrylic-based polymers such as polymethyl methacrylate, styrene-based polymers such as polystyrene or acrylonitrile-styrene copolymer (AS resin), and polycarbonate-based polymers. In addition, polyolefin-based polymers such as polyethylene, polypropylene, polyolefins having a cyclo- or norbornene structure, or ethylene-propylene copolymers, vinyl chloride-based polymers, amide-based polymers such as nylon or aromatic polyamides, imide-based polymers, sulfone-based polymers, polyethersulfone-based polymers, polyetheretherketone-based polymers, polyphenylene sulfide-based polymers, vinyl alcohol-based polymers, vinylidene chloride-based polymers, vinyl butyral-based polymers, allylate-based polymers, polyoxymethylene-based polymers, epoxy-based polymers, or blends of the above polymers may also be cited as examples of polymers forming the transparent protective film. The transparent protective film may contain one or more of any suitable additives. Examples of additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, etc. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100 mass%, more preferably 50 to 99 mass%, even more preferably 60 to 98 mass%, and particularly preferably 70 to 97 mass%. If the content of the thermoplastic resin in the transparent protective film is 50 mass% or less, there is a concern that the high transparency inherent to the thermoplastic resin may not be sufficiently expressed.
[0058] The polarizer protection film of the present invention may use a phase difference film of the resin film. Examples of phase difference films include one having a front phase difference of 40 nm or more and / or a thickness direction phase difference of 80 nm or more. The front phase difference is typically controlled to a range of 40 to 200 nm, and the thickness direction phase difference is typically controlled to a range of 80 to 300 nm. When a phase difference film is used as a polarizer protection film, thinning can be achieved because the phase difference film also functions as a polarizer protection film.
[0059] Examples of phase difference films include birefringent films formed by uniaxial or biaxial stretching of a thermoplastic resin film. The temperature and stretching ratio of the stretching are appropriately set according to the phase difference value, the material of the film, and the thickness.
[0060] The thickness of the above transparent protective film can be appropriately determined, but generally, it is about 1 to 500 μm in terms of strength, workability such as handling, and thinness. In particular, 1 to 300 μm is preferred, and 5 to 200 μm is more preferred.
[0061] On the surface of the transparent protective film where the polarizer is not adhered, a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, or an anti-glare layer may be formed. In addition, the functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, or the anti-glare layer may be formed not only on the transparent protective film itself, but also separately as a distinct component from the transparent protective film.
[0062] An adhesive is used for the bonding process between the polarizer and the transparent protective film. Examples of adhesives include isocyanate-based adhesives, polyvinyl alcohol-based adhesives, gelatin-based adhesives, vinyl latex-based adhesives, water-based polyesters, etc. The above adhesive is typically used as an adhesive composed of an aqueous solution and is typically composed of 0.5 to 60 weight% of solids. In addition to the above, examples of adhesives for the polarizer and the transparent protective film include UV-curing adhesives and electron beam-curing adhesives. Electron beam-curing adhesives for polarizing films exhibit desirable adhesion to the various transparent protective films mentioned above. Furthermore, the adhesive used in the present invention may contain a metal compound filler.
[0063] The coating method of the adhesive is appropriately selected according to the viscosity of the adhesive or the desired thickness. Examples of coating methods include, for instance, reverse coaters, gravure coaters (direct, reverse, or offset), bar reverse coaters, roll coaters, die coaters, bar coaters, and rod coaters. In addition, methods such as dipping can be appropriately used for coating.
[0064] In addition, when using a water-based adhesive or the like, it is preferable to perform the coating of the adhesive such that the thickness of the finally formed adhesive layer is 30 to 300 nm. More preferably, the thickness of the adhesive layer is 60 to 250 nm. On the other hand, when using a curable adhesive, it is preferable to perform the coating such that the thickness of the adhesive layer is 0.1 to 200 μm. More preferably, it is 0.5 to 50 μm, and even more preferably, 0.5 to 10 μm.
[0065] In addition, when laminating a polarizer and a transparent protective film, an easy-to-adhesion layer may be formed between the transparent protective film and the adhesive layer. The easy-to-adhesion layer may be formed by various resins having, for example, a polyester backbone, a polyether backbone, a polycarbonate backbone, a polyurethane backbone, a silicone-based backbone, a polyamide backbone, a polyimide backbone, a polyvinyl alcohol backbone, etc. These polymer resins may be used individually or in combination of two or more types. In addition, other additives may be added to form the easy-to-adhesion layer. Specifically, additionally, tackifiers, UV absorbers, antioxidants, stabilizers such as heat stabilizers, etc. may be used.
[0066] Typically, an easy-adhesion layer is pre-formed on a transparent protective film, and the side of the easy-adhesion layer of the transparent protective film is laminated to a polarizer using an adhesive layer. The formation of the easy-adhesion layer is carried out by coating and drying a material for forming the easy-adhesion layer onto the transparent protective film using a known technique. The material for forming the easy-adhesion layer is typically adjusted to a solution diluted to an appropriate concentration, taking into account the thickness after drying and the smoothness of coating. The thickness of the easy-adhesion layer after drying is preferably 0.01 to 5 μm, more preferably 0.02 to 2 μm, and even more preferably 0.05 to 1 μm. Additionally, the easy-adhesion layer may be formed in multiple layers, but even in this case, it is preferable that the total thickness of the easy-adhesion layer be within the above range.
[0067] <Process (2)>
[0068] In process (2), the resin substrate (3) is peeled off from the protective polarizing film (A) on which the resin substrate is formed.
[0069] <Process (3)>
[0070] In process (3), an activation treatment is performed on the surface of a polarizer (1) from which the resin substrate (3) has been peeled off from the protective polarizing film (A) on which the resin substrate is formed by process (2). In FIGS. 1 and 2, the means for performing the activation treatment is shown as an activation means (4).
[0071] Examples of activation treatments include corona treatment, plasma treatment, excimer treatment, glow treatment, and ozone treatment. Corona treatment can be performed, for example, by discharging in atmospheric air using a corona treatment device manufactured by Kasuga Electric Co. Plasma treatment can be performed, for example, by discharging in atmospheric air or in an inert gas atmosphere such as nitrogen or argon using a plasma discharge device manufactured by Sekisui Chemical Co. Excimer treatment can be performed by irradiating with an excimer lamp. An excimer lamp is a UV lamp with a wavelength of 180 nm or less that encapsulates Xe. Glow treatment and ozone treatment can also be performed according to conventional methods. Among these, corona treatment, plasma treatment, or excimer treatment are preferred in terms of equipment and processing costs. In particular, corona treatment or plasma treatment is preferred because it is easy to control the activation energy.
[0072] The above activation treatment is typically performed under conditions where the activation energy is 0.01 to 2 J / cm². When the activation energy is less than 0.01 J / cm², the activation treatment is insufficient, and foreign substances on the polarizer surface cannot be sufficiently reduced, resulting in insufficient durability (adhesion, appearance). On the other hand, when the activation treatment energy exceeds 2 J / cm², the damage imparted to the polarizer surface tends to increase, raising concerns that optical properties (optical durability) may not be satisfied. Furthermore, when the activation treatment energy exceeds 2 J / cm², while residual foreign substances accompanying the peeling of the resin substrate on the polarizer surface can be reduced, there is a risk of foreign substances being generated due to the damage, which may instead result in insufficient durability (adhesion, appearance). In the above activation treatment, the activation energy is preferably 0.01 to 0.59 J / cm², and also preferably 0.4 to 0.59 J / cm².
[0073] In addition, for example, if the above activation treatment is a corona treatment, the condition for the activation amount (discharge amount: W / m² / min) is preferably 2 to 83 W / m² / min, also preferably 2 to 42 W / m² / min, and further preferably 34 to 42 W / m² / min. In addition, the gap between the electrode and the sample (polarizer) is typically preferably about 1 to 5 mm, and also preferably 1 to 2 mm.
[0074] <Process (4)>
[0075] In process (4), an adhesive layer (5) is directly laminated onto the surface of the polarizer (1) in which process (3) is performed to manufacture a protective polarizing film (B) with an adhesive layer formed thereon. In FIGS. 1 and 2, a separator (6) is formed on the adhesive layer (5) of the protective polarizing film (B) with an adhesive layer formed thereon.
[0076] The above adhesive layer is formed from an adhesive. Various adhesives may be used as the adhesive, and examples include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinylalkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinylpyrrolidone-based adhesives, polyacrylamide-based adhesives, cellulose-based adhesives, etc. An adhesive base polymer is selected according to the type of adhesive.
[0077] Among the above adhesives, acrylic adhesives are preferably used because they exhibit excellent optical transparency, appropriate wettability, cohesiveness, and adhesive properties, as well as excellent weather resistance and heat resistance. Acrylic adhesives include (meth)acrylic polymers as base polymers. (Meth)acrylic polymers typically contain alkyl (meth)acrylates as monomer units as a main component. Furthermore, (meth)acrylates refer to acrylates and / or methacrylates, and have the same meaning as (meth) in the present invention.
[0078] Examples of alkyl (meth)acrylates constituting the main backbone of a (meth)acrylic polymer include straight-chain or branched-chain alkyl groups having 1 to 18 carbon atoms. For example, examples of the alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, amyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isomyristyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, etc. These may be used alone or in combination. It is preferable that the average number of carbon atoms of these alkyl groups is 3 to 9.
[0079] In addition, alkyl (meth)acrylates containing aromatic rings, such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate, can be used in terms of adhesive properties, durability, adjustment of phase difference, and adjustment of refractive index. Alkyl (meth)acrylates containing aromatic rings can be used by mixing a polymer obtained by polymerizing them with the (meth)acrylate-based polymers exemplified above, but from the perspective of transparency, it is preferable to use alkyl (meth)acrylates containing aromatic rings by copolymerizing them with the alkyl (meth)acrylates.
[0080] In the (meth)acrylic polymer, the proportion of the alkyl (meth)acrylate containing the aromatic ring may be 50 weight% or less in weight ratio of the total constituent monomer (100 weight%) of the (meth)acrylic polymer. Furthermore, the content of the alkyl (meth)acrylate containing the aromatic ring is preferably 1 to 35 weight%, preferably 1 to 20 weight%, preferably 7 to 18 weight%, and preferably 10 to 16 weight%.
[0081] Among the above (meth)acrylic polymers, one or more copolymer monomers having polymerizable functional groups having unsaturated double bonds, such as (meth)acryloyl groups or vinyl groups, may be introduced by copolymerization for the purpose of improving adhesion or heat resistance. Specific examples of such copolymer monomers include, for example, hydroxyl group-containing monomers such as (meth)acrylic acid 2-hydroxyethyl, (meth)acrylic acid 3-hydroxypropyl, (meth)acrylic acid 4-hydroxybutyl, (meth)acrylic acid 6-hydroxyhexyl, (meth)acrylic acid 8-hydroxyoctyl, (meth)acrylic acid 10-hydroxydecyl, (meth)acrylic acid 12-hydroxylauryl, or (4-hydroxymethylcyclohexyl)-methylacrylate; Examples include monomers containing carboxyl groups such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; monomers containing acid anhydrides such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; monomers containing sulfonic acid groups such as styrenesulfonic acid or allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; and monomers containing phosphate groups such as 2-hydroxyethylacryloylphosphate.
[0082] In addition, (N-substituted) amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide; (meth)acrylate alkylaminoalkyl monomers such as (meth)acrylate aminoethyl, (meth)acrylate N,N-dimethylaminoethyl, (meth)acrylate t-butylaminoethyl; (meth)acrylate alkoxyalkyl monomers such as (meth)acrylate methoxyethyl, (meth)acrylate ethoxyethyl; Succinimide-based monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide, and N-acryloylmorpholine; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; and itaconimide-based monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide can also be cited as examples of monomers for modification purposes.
[0083] Additionally, as modified monomers, vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinylcarboxylic acid amides, styrene, α-methylstyrene, N-vinylcaprolactam, etc.; cyanoacrylate monomers such as acrylonitrile, methacrylonitrile, etc.; epoxy group-containing acrylic monomers such as (meth)acrylate glycidyl, etc.; glycol-based acrylic ester monomers such as (meth)acrylate polyethylene glycol, (meth)acrylate polypropylene glycol, (meth)acrylate methoxyethylene glycol, (meth)acrylate methoxypolypropylene glycol, etc.; Acrylic acid ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicon (meth)acrylate, or 2-methoxyethylacrylate can also be used. In addition, isoprene, butadiene, isobutylene, vinyl ether, etc. may be used.
[0084] In addition, copolymerizable monomers other than those mentioned above may include silane-based monomers containing silicon atoms. Examples of silane-based monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc.
[0085] In addition, as copolymer monomers, polyfunctional monomers having two or more unsaturated double bonds such as (meth)acryloyl groups, vinyl groups, etc., esters of (meth)acrylic acids and polyhydric alcohols such as tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate, or on a backbone such as polyester, epoxy, or urethane Polyester (meth)acrylate, epoxy (meth)acrylate, urethane (meth)acrylate, etc., having two or more unsaturated double bonds such as (meth)acryloyl groups and vinyl groups added as functional groups identical to the monomer components may also be used.
[0086] The (meth)acrylic polymer is composed mainly of alkyl (meth)acrylates in the weight ratio of the total constituent monomers, and the ratio of the copolymer monomer in the (meth)acrylic polymer is not particularly limited, but the ratio of the copolymer monomer is preferably about 0 to 20%, about 0.1 to 15%, and further about 0.1 to 10% in the weight ratio of the total constituent monomers.
[0087] Among these copolymer monomers, hydroxyl group-containing monomers are preferably used in terms of adhesion and durability. Since hydroxyl group-containing monomers have high reactivity with intermolecular crosslinking agents, they are preferably used to improve the cohesiveness or heat resistance of the resulting adhesive layer. Hydroxyl group-containing monomers are preferred in terms of reworkability. When hydroxyl group-containing monomers are included as copolymer monomers, the proportion is preferably 0.01 to 15 weight%, more preferably 0.03 to 10 weight%, and further preferably 0.05 to 7 weight%.
[0088] Carboxyl group-containing monomers are desirable for achieving both durability and reworkability. When a copolymer monomer contains a carboxyl group-containing monomer, the proportion is preferably 0.05 to 10 weight%. Setting the proportion of the carboxyl group-containing monomer within the above range is desirable for suppressing foreign substances remaining on the surface of the polarizer from migrating to the adhesive layer following the peeling of the resin substrate. The proportion of the carboxyl group-containing monomer is particularly effective when it is 4 weight% or less. The proportion of the carboxyl group-containing monomer is preferably 0.05 to 4 weight%, more preferably 0.1 to 3 weight%, and further preferably 0.2 to 2 weight%.
[0089] The (meth)acrylic polymer of the present invention is typically used with a weight-average molecular weight in the range of 500,000 to 3,000,000. Considering durability, particularly heat resistance, it is preferable to use one with a weight-average molecular weight of 700,000 to 2,700,000. It is also preferable to use one with a weight-average molecular weight of 800,000 to 2,500,000. If the weight-average molecular weight is less than 500,000, it is undesirable in terms of heat resistance. Furthermore, if the weight-average molecular weight exceeds 3,000,000, a large amount of diluent is required to adjust the viscosity for coating, which is undesirable in terms of increased costs. In addition, the weight-average molecular weight refers to a value calculated by polystyrene conversion after measuring by GPC (Gel Permeation Chromatography).
[0090] For the preparation of such (meth)acrylic polymers, known methods such as solution polymerization, bulk polymerization, emulsion polymerization, and various radical polymerizations can be appropriately selected. Furthermore, the obtained (meth)acrylic polymer may be any of the following: random copolymer, block copolymer, graft copolymer, etc.
[0091] In addition, for solution polymerization, for example, ethyl acetate, toluene, etc. are used as polymerization solvents. As a specific example of solution polymerization, the reaction is carried out under reaction conditions of about 50 to 70°C for about 5 to 30 hours by adding a polymerization initiator under an inert gas stream such as nitrogen.
[0092] The polymerization initiators, chain transfer agents, emulsifiers, etc. used in radical polymerization are not particularly limited and can be appropriately selected and used. Furthermore, the weight-average molecular weight of the (meth)acrylic polymer can be controlled by the amount of polymerization initiator and chain transfer agent used and the reaction conditions, and their amounts are appropriately adjusted according to their types.
[0093] As polymerization initiators, for example, azo-based initiators such as 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazoline-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (manufactured by Wako Jun Pharmacy, VA-057), persulfates such as potassium persulfate and ammonium persulfate, and di(2-ethylhexyl)peroxydicarbonate, Examples include peroxide-based initiators such as di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutylate, 1,1-di(t-hexylperoxy)cyclohexane, t-butylhydroperoxide, and hydrogen peroxide; redox-based initiators combining peroxides with reducing agents, such as combinations of persulfate and sodium bisulfite, and combinations of peroxide and sodium ascorbate; but to these It is not limited.
[0094] The above polymerization initiator may be used alone or in a mixture of two or more types, but the total content is preferably about 0.005 to 1 part by weight per 100 parts by weight of monomer, and more preferably about 0.02 to 0.5 parts by weight.
[0095] In addition, when preparing a (meth)acrylic polymer of the above weight-average molecular weight using, for example, 2,2'-azobisisobutyronitrile as a polymerization initiator, it is preferable that the amount of polymerization initiator used be about 0.06 to 0.2 parts by weight and about 0.08 to 0.175 parts by weight per 100 parts by weight of the total amount of monomer components.
[0096] Examples of chain transfer agents include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglucholic acid, 2,3-dimercapto-1-propanol, etc. The chain transfer agent may be used alone or in a mixture of two or more types, but the total content is about 0.1 parts by weight or less per 100 parts by weight of the total amount of monomer components.
[0097] In addition, emulsifiers used in cases of emulsion polymerization include, for example, anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, ammonium polyoxyethylene alkyl ether sulfate, and sodium polyoxyethylene alkylphenyl ether sulfate, and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene fatty acid ester, and polyoxyethylene-polyoxypropylene block polymer. These emulsifiers may be used alone or in combination of two or more types.
[0098] In addition, as a reactive emulsifier, there are emulsifiers to which radical polymerizable functional groups such as propenyl groups and allyl ether groups have been introduced, specifically, examples include Aquaron HS-10, HS-20, KH-10, BC-05, BC-10, BC-20 (all manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), Adecariasop SE10N (manufactured by Asahi Telecom). Since the reactive emulsifier is blown into the polymer chain after polymerization, it is desirable for water resistance to be improved. The amount of emulsifier used is 0.3 to 5 parts by weight per 100 parts by weight of the total amount of monomer components, and 0.5 to 1 part by weight is more preferable due to polymerization stability and mechanical stability.
[0099] In addition, the adhesive of the present invention may contain a crosslinking agent. As a crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate may be used. Examples of organic crosslinking agents include isocyanate-based crosslinking agents, peroxide-based crosslinking agents, epoxy-based crosslinking agents, and imine-based crosslinking agents. A polyfunctional metal chelate is one in which a polyvalent metal is covalently bonded or coordinately bonded with an organic compound. Examples of polyvalent metal atoms include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. Examples of atoms in the organic compound that form covalent or coordinate bonds include oxygen atoms, and examples of organic compounds include alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds.
[0100] The amount of crosslinking agent used is preferably 0.01 to 20 parts by weight and also preferably 0.03 to 10 parts by weight per 100 parts by weight of base polymer (e.g., (meth)acrylic polymer). Furthermore, if the amount of crosslinking agent is less than 0.01 parts by weight, the adhesive tends to have insufficient cohesive strength, which may cause foaming when heated, whereas if it is more than 20 parts by weight, the moisture resistance is insufficient, making it prone to peeling during reliability tests, etc.
[0101] In addition, the adhesive of the present invention may contain a silane coupling agent. By using a silane coupling agent, durability can be improved. As silane coupling agents, specifically, for example, epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silanes such as 3-isocyanatepropyltriethoxysilane. Examples include coupling agents.
[0102] The above silane coupling agent may be used alone or in a mixture of two or more types, but the total content is preferably 0.001 to 5 parts by weight of the silane coupling agent per 100 parts by weight of the above (meth)acrylic polymer, more preferably 0.01 to 1 part by weight, more preferably 0.02 to 1 part by weight, and more preferably 0.05 to 0.6 parts by weight. This is an amount that improves durability and appropriately maintains adhesion to optical members such as liquid crystal cells.
[0103] In addition, the adhesive composition of the present invention may contain other known additives, and may appropriately add, for example, ionic compounds, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, granular materials, thin films, etc., depending on the application. Furthermore, within a controllable range, a redox system with a reducing agent added may be employed.
[0104] The adhesive layer is formed by a method such as, for example, applying the adhesive to a separator that has undergone a peeling treatment, drying and removing a polymerizing solvent, and then transferring the adhesive layer to a polarizer, or by applying the adhesive to a polarizer and drying and removing a polymerizing solvent to form an adhesive layer on the polarizer. Additionally, when applying the adhesive, one or more solvents other than the polymerizing solvent may be newly added as appropriate.
[0105] A silicone release liner is preferably used as the release-treated separator. In the process of forming an adhesive layer by applying and drying the adhesive of the present invention onto such a liner, a suitable method for drying the adhesive may be appropriately employed depending on the purpose. Preferably, a method of heat-drying the coating film is used. The heat-drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. By setting the heating temperature within the above range, an adhesive having excellent adhesive properties can be obtained.
[0106] The drying time may be appropriately used. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 10 minutes, and particularly preferably 10 seconds to 5 minutes.
[0107] Various methods are used to form the adhesive layer. Specifically, examples include extrusion coating methods using roll coat, kiss roll coat, gravure coat, reverse coat, roll brush, spray coat, dip roll coat, bar coat, knife coat, air knife coat, curtain coat, rip coat, die coater, etc.
[0108] The thickness of the adhesive layer is not particularly limited and, for example, is about 1 to 100 μm. Preferably, it is 2 to 50 μm, more preferably 2 to 40 μm, and even more preferably 5 to 35 μm.
[0109] If the above adhesive layer is exposed, the adhesive layer may be protected with a peel-off sheet (separator) until it is provided for practical use.
[0110] Suitable materials for the separator include, for example, plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester films, porous materials such as paper, cloth, and non-woven fabric, nets, foamed sheets, metal foils, and laminates thereof, but plastic films are preferably used because they have excellent surface smoothness.
[0111] The plastic film is not particularly limited as long as it is a film capable of protecting the adhesive layer, and examples include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, etc.
[0112] The thickness of the separator is typically 5 to 200 μm, preferably 5 to 100 μm. Depending on the needs, the separator may be subjected to release and antifouling treatments using silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release agents, silica powder, etc., or antistatic treatments such as coating, mixing, or deposition. In particular, by appropriately performing a peeling treatment such as silicone treatment, long-chain alkyl treatment, or fluorine treatment on the surface of the separator, the peelability from the adhesive layer can be further improved.
[0113] In addition, the method for manufacturing a protective polarizing film having an adhesive layer formed thereon according to the present invention has the above processes (1) to (4), but may include process (5) as shown in FIG. 2.
[0114] <Process (5)>
[0115] Process (5) relates to a process of laminating a surface protection film (7) onto the surface of a polarizer (1), from which the resin substrate (3) has been peeled off by process (2), between process (2) and process (3), and then peeling it off. In FIG. 2, process (5)-1 shows the process of laminating the surface protection film (7), and process (5)-2 shows the process of peeling it off after lamination.
[0116] The surface protection film (7) is typically used to temporarily protect the surface of the polarizer (1) during the process from after process (2) to process (4). While the surface protection film (7) temporarily protects the surface of the polarizer (1), it is assumed that after peeling off from the surface of the polarizer (1), adhesives related to the surface protection film (7) remain as foreign substances on the surface of the polarizer (1). However, in the present invention, even when the surface of the polarizer (1) is temporarily protected by the surface protection film (7) by process (5), an activation treatment is performed by process (3), so the problem of foreign substances remaining on the surface of the polarizer (1) caused by adhesives related to the surface protection film (7) can also be resolved.
[0117] <Surface protection film>
[0118] A surface protection film typically comprises a base film and an adhesive layer, and protects a polarizer by interposing the adhesive layer.
[0119] As the substrate film for the surface protection film, a film material that is isotropic or close to isotropic is selected from the perspective of inspectability or manageability. Examples of such film materials include transparent polymers such as polyester resins (e.g., polyethylene terephthalate film), cellulose resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, and acrylic resins. Among these, polyester resins are preferred. The substrate film may be used as a laminate of one or more film materials, or an extended product of the above film may be used. The thickness of the substrate film is generally 500 μm or less, preferably 10 to 200 μm.
[0120] As an adhesive forming the adhesive layer of a surface protection film, an adhesive having a base polymer such as a (meth)acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based or rubber-based polymer can be appropriately selected and used. From the perspective of transparency, weather resistance, and heat resistance, an acrylic adhesive having an acrylic polymer as a base polymer is preferred. The thickness of the adhesive layer (dry film thickness) is determined according to the required adhesive strength. Typically, it is about 1 to 100 μm, preferably 5 to 50 μm.
[0121] In addition, on the surface protection film, a release treatment layer can be formed on the opposite side of the surface on which the adhesive layer is formed in the substrate film by means of a low-adhesion material such as silicone treatment, long-chain alkyl treatment, or fluorine treatment.
[0122] The protective polarizing film formed with an adhesive layer according to the present invention can be used in practice as an optical film laminated with other optical layers. Although there are no particular limitations on the optical layers, one or more layers may be used, such as optical layers that are used in forming liquid crystal display devices, such as reflectors, transmissive plates, phase difference plates (including wavelength plates such as 1 / 2 or 1 / 4), and visual compensation films. In particular, a reflective polarizing film or a transmissive polarizing film formed by laminating a reflector or a transmissive reflector in addition to the protective polarizing film formed with an adhesive layer according to the present invention, an elliptical polarizing film or a circular polarizing film formed by laminating a phase difference plate in addition to the polarizing film, a wide viewing angle polarizing film formed by laminating a visual compensation film in addition to the polarizing film, or a polarizing film formed by laminating a brightness enhancement film in addition to the polarizing film is preferred.
[0123] An optical film formed by laminating the optical layer onto a polarizing film having an adhesive layer can be formed by sequentially laminating them separately during the manufacturing process of a liquid crystal display device, etc. However, forming the optical film by laminating them in advance offers the advantage of improving the manufacturing process of the liquid crystal display device, etc., due to superior quality stability and assembly work. Suitable adhesive means, such as an adhesive layer, may be used for lamination. In bonding the polarizing film having the adhesive layer or other optical films, their optical axes can be arranged at an appropriate angle according to the desired phase difference characteristics.
[0124] The protective polarizing film or optical film formed with an adhesive layer according to the present invention can be preferably used for the formation of various devices, such as liquid crystal display devices. The formation of a liquid crystal display device can be carried out in accordance with conventional methods. That is, a liquid crystal display device is generally formed by assembling a liquid crystal cell, a protective polarizing film or optical film with an adhesive layer formed thereon, and, if necessary, components such as a lighting system, and assembling a driving circuit. However, in the present invention, there are no particular limitations except for the use of the protective polarizing film or optical film with an adhesive layer formed thereon according to the present invention, and it can be carried out in accordance with conventional methods. Regarding the liquid crystal cell, any type such as a TN type, STN type, or π type can be used.
[0125] Suitable liquid crystal display devices can be formed, such as a liquid crystal display device in which a protective polarizing film or an optical film having an adhesive layer formed on one or both sides of a liquid crystal cell is disposed, or a backlight or a reflector is used in a lighting system. In that case, the protective polarizing film or the optical film having an adhesive layer formed according to the present invention may be installed on one or both sides of the liquid crystal cell. When forming a protective polarizing film or an optical film having an adhesive layer formed on both sides, they may be the same or different. Furthermore, in forming the liquid crystal display device, suitable components such as a diffuser, an anti-glare layer, an anti-reflective film, a protective plate, a prism array, a lens array sheet, a light diffuser, and a backlight may be disposed in one or two or more layers at appropriate locations.
[0126] Examples
[0127] The present invention will be specifically described below by way of examples, but the present invention is not limited by these examples. Also, parts and % in each example are all based on weight. A protective polarizing film was manufactured.
[0128] <Optical Film Laminate: Fabrication of Thin Polarizing Film on Resin Substrate>
[0129] To fabricate a thin polarizing film, first, a laminate having a 9 μm thick PVA layer formed on an amorphous PET substrate was stretched by air-assisted stretching at a stretching temperature of 130 °C to form a stretched laminate, and next, the stretched laminate was dyed to form a colored laminate, and the colored laminate was stretched integrally with the amorphous PET substrate by boric acid water stretching at a stretching temperature of 65 °C to achieve a total stretching ratio of 5.94 times, and then dried at 50 °C for 4 minutes to form an optical film laminate containing a 4 μm thick PVA layer. Through such two-stage stretching, it was possible to produce an optical film laminate containing a 4 μm thick PVA layer, in which the PVA molecules of the PVA layer formed on the amorphous PET substrate are oriented in a higher order, and the iodine adsorbed by dyeing is oriented in a higher order as a polyiodide ion complex in one direction, thereby constituting a high-performance polarizing film.
[0130] <Transparent Protective Film>
[0131] A (met)acrylic resin film with a thickness of 40 μm (manufactured by Toyo Steel Co., Ltd., Product Name: HX-40UC) was used.
[0132] <Preparation of an adhesive layer with a separator>
[0133] After applying the following adhesive (solution) 1 or 2 to the surface of a polyethylene terephthalate film (separator film) treated with a silicone-based release agent, the film was dried in an air-circulating constant temperature oven at 150°C for 60 seconds to form an adhesive layer with a thickness of 20 μm, thereby obtaining an adhesive layer with a separator formed thereon.
[0134] ≪Adhesive 1≫
[0135] <Preparation of Acrylic Polymer (A1)>
[0136] A monomer mixture containing 94.9 parts butyl acrylate, 0.1 parts 2-hydroxyethyl acrylate, and 5 parts acrylic acid was injected into a 4-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Additionally, 0.1 parts 2,2'-azobisisobutyronitrile was injected along with ethyl acetate as a polymerization initiator for 100 parts of the monomer mixture (solid content), and nitrogen gas was introduced while stirring slowly to purify the atmosphere. Then, the liquid temperature inside the flask was maintained at around 60°C, and a polymerization reaction was carried out for 7 hours. Afterward, ethyl acetate was added to the resulting reaction solution to prepare a solution of an acrylic polymer (A1) with a weight-average molecular weight of 2 million, adjusted to a solid content concentration of 20%.
[0137] <Preparation of Adhesive Composition>
[0138] An acrylic adhesive solution was prepared by mixing 0.1 parts of trimethylolpropanexylylene diisocyanate (manufactured by Mitsui Chemical Co., Ltd.: Takenate D110N), 0.3 parts of dibenzoyl peroxide, and 0.075 parts of γ-glycidoxypropylmethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-403) with respect to 100 parts of the solid content of the acrylic polymer (A1) solution obtained above.
[0139] ≪Adhesive 2≫
[0140] <Preparation of Acrylic Polymer (A2)>
[0141] A solution of an acrylic polymer (A2) with a weight average molecular weight of 1.6 million was prepared in the same manner as in Preparation Example 1, except that a monomer mixture containing 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate was used as the monomer mixture.
[0142] <Preparation of Adhesive Composition>
[0143] An acrylic adhesive solution was prepared by mixing 0.1 parts of trimethylolpropanetolylene diisocyanate (manufactured by Nippon Polyurethane Co., Ltd.: Colonate L), 0.3 parts of dibenzoyl peroxide, and 0.075 parts of γ-glycidoxypropylmethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-403) with respect to 100 parts of the solid content of the acrylic polymer (A2) solution obtained above.
[0144] Example 1
[0145] (Process 1)
[0146] A transparent protective film was laminated onto the surface of a polarizing film (polarizer) in the above optical film laminate (thin polarizing film formed on a resin substrate) while coating it with a polyvinyl alcohol-based adhesive, thereby preparing a polarizing protective film formed on a resin substrate.
[0147] (Process 2)
[0148] Next, an amorphous PET substrate was peeled off from a protective polarizing film on which a resin substrate was formed.
[0149] (Process 3)
[0150] Next, corona treatment was performed on the surface (single side) of the polarizing film (polarizer) from which the amorphous PET substrate was peeled off by the above process (2) using a corona irradiator (manufactured by Kasuga Electric Co., CT-0212) under conditions of 0.5 J / ㎠.
[0151] (Process 4)
[0152] Next, the adhesive layer (using adhesive 1) formed in the manufacture of an adhesive layer with a separator formed on the surface of the polarizing film (polarizer) in which the above process (3) was performed is laminated to obtain a polarizing protective film with an adhesive layer formed thereon.
[0153] Examples 2 to 17, Comparative Examples 1 to 3
[0154] In Example 1, a protective polarizing film with an adhesive layer formed thereon was produced in the same manner as in Example 1, except that the means of activation treatment or the total amount of irradiation used in process (3) and the type of adhesive used in process (4) were changed as shown in Table 1.
[0155] In addition, in Examples 8 and 17, as shown in FIG. 2, a process (5) of peeling off a surface protection film after laminating it on the surface of a polarizer was formed between process (2) and process (3). The surface protection film used was Toretec 7832C manufactured by Tore Corporation.
[0156] In addition, as shown in Table 1, the "plasma" used was (manufactured by Kasuga Electric Co., Ltd., APW-602f), and the "excimer" used was (Ushio Electric Co., Ltd., SUS05). Comparative Example 3 is a case where no activation treatment was performed.
[0157] [evaluation]
[0158] The following evaluations were performed on the protective polarizing films with adhesive layers formed thereon obtained in the examples and comparative examples. The results are shown in Table 1. For durability, "adhesion strength" and "peeling" and "appearance" after a predetermined test were evaluated. For optical durability, "discoloration" and "hot water test" after a predetermined test were evaluated.
[0159] <Measurement of Oligomer Amount in Adhesive Layer>
[0160] A polarizing film with an adhesive layer formed (separator formed) was left for 500 hours under conditions of 60°C and 90% RH, after which the separator was removed. Approximately 0.025 g of the adhesive layer (sample) was taken from the polarizing film with the adhesive layer formed, 1 ml of chloroform was added, and the mixture was shaken at room temperature for 18 hours. Then, 5 ml of acetonitrile was added for extraction, followed by shaking for 3 hours. The obtained solution was filtered through a 0.45 ml membrane filter to prepare the sample. A standard of trimeric PET oligomer was adjusted to a constant concentration, a calibration curve was constructed, and the amount of PET oligomer (ppm) contained in the adhesive was determined using the calibration curve. The calibration curve was constructed by measuring the PET oligomer concentration (ppm) using a sample with a known concentration via HPLC.
[0161] HPLC Device: Agilent Technologies 1200 Series
[0162] Measurement conditions
[0163] Column: ZORBAX SB-C18 manufactured by Agilent Technologies
[0164] Column temperature: 40 ℃
[0165] Column flow rate: 0.8 ml / min
[0166] Eluent composition: Water / acetonitrile reverse phase gradient condition
[0167] Injection volume: 5 µl
[0168] Detector: PDA
[0169] Quantification method: A standard sample of PET oligomer trimer was dissolved in chloroform and then diluted with acetonitrile to adjust the sample to a constant concentration. A calibration curve was constructed from the HPLC area and the adjusted concentration, and the amount of PET oligomer in the sample was determined.
[0170] It is preferable that the PET oligomer content be 50 ppm or less, 10 ppm or less, and furthermore 5 ppm or less.
[0171] <Adhesion>
[0172] A protective polarizing film (separator formed) with an adhesive layer formed thereon was cut to a width of 25 mm × a length of approximately 100 mm and used as an evaluation sample. After removing the separator from the sample, the adhesive layer was applied to an alkali-free glass plate (manufactured by Corning, 1737) with a thickness of 0.5 mm using a 2 kg reciprocating roll, and after being left to stand at room temperature (23 ℃) for 1 hour, the adhesion strength (N / 25 mm) was measured at a peel angle of 90° and a peel speed of 300 mm / min.
[0173] <Exfoliation and Appearance>
[0174] Two samples were prepared as evaluation samples by cutting a protective polarizing film (separator forming) with an adhesive layer to a size of 15 inches. After peeling off the separator from the sample, each sample was bonded to both sides of an alkali-free glass (manufactured by Corning, 1737) with a thickness of 0.5 mm using a laminator so that each sample was cross-nicol. Subsequently, the samples were autoclaved at 50°C and 0.5 MPa for 15 minutes to completely adhere them to the acrylic-free glass. After treating the samples subjected to this process, the samples were treated for 500 hours under the respective atmospheres of 60°C / 90% RH (humidification condition) and 80°C (heating condition), and then peeling and appearance were evaluated.
[0175] ≪Exfoliation≫
[0176] Samples treated under humidification or heating conditions were evaluated visually according to the following criteria.
[0177] ◎ : No peeling or foaming was observed at all.
[0178] ○ : Delamination or foaming that is not visible to the naked eye was confirmed.
[0179] △ : Small peeling or foaming visible to the naked eye was observed.
[0180] × : Clear peeling or foaming was confirmed.
[0181] ≪Exterior≫
[0182] A polarizing film X was prepared separately by adhering the above-mentioned transparent protective film only to one side of a polarizer with a polarization degree of 99.98. A laminate was prepared by placing the polarizer side of the polarizing film X and the side of the adhesive layer of a sample treated under humidification or heating conditions facing each other, and arranging them in a cross-nicol configuration. The polarizing film X and the sample were placed in a space of 300 mm or less. Light of 13,000 cd / m² or more was shone from the side of the polarizing film X of the laminate, and whether a bright spot caused by foreign substances (such as PET oligomers) could be confirmed was evaluated using a microscope (200x magnification) according to the following criteria.
[0183] ◎ : Cannot confirm the bright spot.
[0184] × : Bright spots have occurred and affect the display.
[0185] <Bleaching Test>
[0186] A protective polarizing film (separator formation) with an adhesive layer formed thereon was cut to 151 mm × 85 mm and used as an evaluation sample. After peeling off the separator from the sample, it was bonded to alkali-free glass (manufactured by Corning, 1737) with a thickness of 0.5 mm using a laminator. Subsequently, the sample was autoclaved at 50°C and 0.5 MPa for 15 minutes to completely adhere it to the acrylic-free glass. After treating the sample subjected to this process, the amount of discoloration was measured after treatment for 500 hours under an atmosphere of 60°C / 95% RH.
[0187] The amount of decolorization (㎛) was measured using a microscope. It is preferable that the amount of decolorization (㎛) be 500㎛ or less, 50㎛ or less, and furthermore 10㎛ or less.
[0188] <Hot Water Test>
[0189] A polarizing film with an adhesive layer (separator formation) was cut to 25 mm × 50 mm and used as an evaluation sample. After peeling off the separator from the sample, it was bonded to alkali-free glass (manufactured by Corning, 1737) with a thickness of 0.5 mm using a laminator. Subsequently, the sample was autoclaved at 50°C and 0.5 MPa for 15 minutes to ensure complete adhesion to the acrylic-free glass. The sample subjected to this treatment was immersed in hot water at 60°C for 2 hours to conduct a hot water test. Subsequently, the sample subjected to the hot water test was removed, placed in a cross-Nicol for observation, and the area T (mm²) of the portion without light leakage was measured with a ruler. From the results, the polarizer retention rate (%) was calculated using the following formula.
[0190] Polarizer retention rate (%) = (T / 1250) × 100
[0191] It is desirable that the polarizer retention rate (%) be 95% or higher, 96% or higher, and furthermore 98% or higher.
[0192] Explanation of the symbols
[0193] A ; A protective polarizing film formed on a resin substrate B ; Polarizing film with an adhesive layer 1 ; Polarizer 2 ; Transparent protective film 3 ; Resin recording 4 ; Activation means 5 ; Adhesive layer 6 ; Separator 7 ; Surface protection film
Claims
Claim 1 A method for manufacturing a polarizing film having an adhesive layer formed thereon, characterized by having: a process (1) of preparing a polarizing film having a resin substrate and a polarizer formed on one side of the resin substrate, and a transparent protective film laminated on the side of the polarizer; a process (2) of peeling off the resin substrate from the polarizing film having the resin substrate; a process (3) of performing an activation treatment on the surface of the polarizer from which the resin substrate was peeled off by the process (2) under conditions in which the integrated irradiation amount of activation energy is 0.01 to 0.59 J / ㎠; and a process (4) of directly laminating an adhesive layer on the surface of the polarizer on which the process (3) was performed. Claim 2 A method for manufacturing a protective polarizing film having an adhesive layer formed thereon, characterized in that, in claim 1, the activation treatment of the process (3) is corona treatment, plasma treatment, or excimer treatment. Claim 3 A method for manufacturing a protective polarizing film having an adhesive layer formed thereon, characterized in that, in claim 1 or 2, the thickness of the polarizer is 10 μm or less. Claim 4 A method for manufacturing a polarizing film with an adhesive layer formed thereon, wherein, in claim 1 or 2, the polarizer is a polarizing film of a continuous web made of a polyvinyl alcohol-based resin oriented with a dichromatic material, and a laminate comprising a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate is obtained by stretching in a two-stage stretching process consisting of aerial assisted stretching and boric acid underwater stretching. Claim 5 A method for manufacturing a polarizing film with a protective adhesive layer formed thereon, characterized in that, in claim 1 or 2, the resin substrate is an ester-based resin substrate. Claim 6 A method for manufacturing a protective polarizing film having an adhesive layer formed thereon, characterized in that, in claim 1 or 2, the adhesive layer laminated in the process (4) is an acrylic adhesive layer. Claim 7 A method for manufacturing a polarizing film with an adhesive layer formed thereon, characterized in that, in the first or second step, between the first step (2) and the second step (3), a step (5) of laminating a surface protection film onto the surface of a polarizer from which a resin substrate has been peeled off by the second step (2) and then peeling it off.
Citation Information
Patent Citations
Method for manufacturing polarizing plate, polarizing plate, optical film and image display device
JP2009008860A
Surface protective film for optical film
JP2011191768A
Adhesive optical film, manufacturing method for same and image display device using same
KR1020130019005A
